Organic Semiconductor Field-Effect Transistors Based on Organic-2D Heterostructures - Wang, Zi; Huang, Lizhen; Chi, Lifeng (Frontiers in Materials, 2020)
In the past three decades, organic semiconductor field-effect transistors (OFETs) have drawn intense attention as promising candidates for drive circuits of flat panel display, radio frequency identifications, chemical/bio-sensors, and other devices. Generally, the key parameters of OFETs, carrier mobility, threshold voltage, and on/off current ratio are closely related to the degree of order and surface/interface electronic structure of organic semiconductor (OSC) films. The ordering of films is crucially determined by the molecule-substrate interactions. On inert substrates (such as SiO2) OSC films can hardly reach a high degree of ordering without growth templates, while traditional single crystal surfaces usually force the OSC molecules to deviate from their favorite assemble manner resulting in an unstable structure. Recently, the rise of two-dimensional materials (2D) provides a possible solution. The in-plane lattice of 2D materials can offer possible epitaxy templates for OSCs while the weak van der Waals (vdWs) interaction between OSC and 2D layers allows for more flexibility to realize the epitaxy growth of OSCs with their favored assemble manner. In addition, the various band structures tuned by the layer numbers of 2D materials encourage widely modified OSC electronic structures by interface doping between the OSC and 2D layers, which benefits the structure by obtaining high-performance OFETs. In this review, we emphasize and discuss the recent advances of OSC-2D hybrid OFETs. The OSC-2D heterostructures not only promote OFET device performances by film morphology/structure optimization and channel electronic structure modification, but also offer platforms for basic organic solids physics investigation and further functional optoelectronic devices.